Epidemiology of Renal Cell Carcinoma: 2022 Update - Bukavina, Laura; Bensalah, Karim; Bray, Freddie; Carlo, Maria; Challacombe, Ben; Karam, Jose A.; Kassouf, Wassim; Mitchell, Thomas; Montironi, Rodolfo; O'Brien, Tim; Panebianco, Valeria; Scelo, Ghislaine; et al. (European urology, 2022)
We explored the global incidence and mortality of kidney cancer as well as its risk factors. We also highlight germline and somatic mutations that predispose to kidney cancer development. The data provide an insight into the complexity of kidney cancer epidemiology and germline and somatic mutations in patients at risk of developing kidney cancer. International variations in the rates of kidney cancer (KC) are considerable. An understanding of the risk factors for KC development is necessary to generate opportunities to reduce its incidence through prevention and surveillance. To retrieve and summarize global incidence and mortality rates of KC and risk factors associated with its development, and to describe known familial syndromes and genetic alterations that represent biologic risk factors. A systematic review was conducted via Medline (PubMed) and Scopus to include meta-analyses, reviews, and original studies regarding renal cell carcinoma, epidemiology, and risk factors. Our narrative review provides a detailed analysis of KC incidence and mortality, with significant variations across time, geography, and sex. In particular, while KC incidence has continued to increase, mortality models have leveled off. Among the many risk factors, hypertension, obesity, and smoking are the most well established. The emergence of new genetic data coupled with observational data allows for integrated management and surveillance strategies for KC care. KC incidence and mortality rates vary significantly by geography, sex, and age. Associations of the development of KC with modifiable and fixed risk factors such as obesity, hypertension, smoking, and chronic kidney disease (CKD)/end-stage kidney disease (ESKD) are well described. Recent advances in the genetic characterization of these cancers have led to a better understanding of the germline and somatic mutations that predispose patients to KC development, with potential for identification of therapeutic targets that may improve outcomes for these at-risk patients. We reviewed evidence on the occurrence of kidney cancer (KC) around the world. Currently, the main avoidable causes are smoking, obesity, and high blood pressure. Although other risk factors also contribute, prevention and treatment of these three factors provide the best opportunities to reduce the risk of developing KC at present.